Development of 3D needled composite from denim waste and polypropylene fibers for structural applications. (3rd January 2022) - Wang, Shujuan; Zhang, Tao; Zhang, Xiaolin; Ge, Shengbo; Fan, Wei
Graphical abstract: Highlights: A facile method was developed to prepare composites using waste denim and PP fibers. Dyes on denim fiber enhanced the interphase between PP matrix and the reinforcement. The formaldehyde-free composite exhibits excellent water resistance and mechanical properties. The composite with low-cost is an ideal candidate for furniture materials. Abstract: The current study presents a facile yet efficient strategy to the recycling of waste textiles into cost-effective products to reduce environmental pollution. Specifically, the composites were prepared by the denim fibers extracted from the waste denim fabrics and polypropylene fibers through three dimensional needle-punching process and compression moulding. The mechanical properties, 24 h thickness swelling rate and formaldehyde concentration of the developed composites were noted to be better than those of the ordinary high density fiberboard. Overall, the findings from this study demonstrate the successful development of high-performance and low-cost composites as ideal furniture material.